5S IMPROVEMENT PRINCIPLES AND CONTINUOUS IMPROVEMENT IN KAIZEN IN EDUCATIONAL INSTITUTIONS - Rita Afrina; Saifuddin; Jamaluddin (CV. Radja Publika, 2026)
The implementation of 5S and Kaizen principles in the school environment is one effort to create a culture of discipline, cleanliness, orderliness, and continuous improvement orientation. The 5S principles consisting of Seiri (Sorting), Seiton (Organizing), Seiso (Cleaning), Seiketsu (Maintenance/Standardization), and Shitsuke (Diligence/Discipline) can be applied in the management of classrooms, libraries, laboratories, and the school environment in general in order to create a comfortable and conducive learning atmosphere. Meanwhile, Kaizen emphasizes the importance of continuous improvement involving all school members, including teachers, students, and educational staff, in improving the quality of learning and school governance. This paper aims to explain the implementation of 5S and Kaizen principles in the school environment and their impact on discipline, cleanliness, and the effectiveness of teaching and learning activities. The method used in writing this paper is a literature study by collecting various sources from books, journals, and relevant scientific articles. The discussion results show that the implementation of 5S is able to increase students’ awareness of the importance of maintaining cleanliness and neatness in the school environment, while Kaizen encourages the creation of a culture of evaluation and continuous improvement in the educational process. Thus, the implementation of 5S and Kaizen principles can support the creation of a more comfortable, productive, and high-quality school environment.